Outcomes of Capitohamate Bone-Ligament-Bone Grafts for Scapholunate Injury - van Kampen, Robert J.; Bayne, Christopher O.; Moran, Steven L.; Berger, Richard A. (Journal of Wrist Surgery, 2015)
Purpose In an attempt to restore natural carpal kinematics more closely, bone-ligament-bone (BLB) grafts have been described for treating scapholunate (SL) injury. In this article we report the long-term results of capitohamate BLB autograft for the treatment of SL dissociation.Methods The medical records of patients treated with capitohamate BLB grafts for SL dissociation were retrospectively reviewed. Twenty-three patients were available for evaluation. Patients were sent a Disabilities of the Arm, Shoulder, and Hand (DASH) and a Patient-Rated Wrist Evaluation (PRWE) questionnaire and returned for exam. Thirteen patients returned the questionnaire, and 12 wrists were examined. Range of motion, grip strength, pain, complications, return to work, and radiographic parameters were documented.Results The average length of follow-up evaluation was 9.2 years. The average SL gap was 4.5 mm preoperatively and 3.6 mm at final follow-up. The average SL angle was 70 degrees preoperatively and 73 degrees at final follow-up. There was no statistically significant difference in preoperative versus postoperative flexion, extension, radial deviation, ulnar deviation, or grip strength. The average postoperative visual analog scale (VAS) score was 1.25 at rest and 3.58 with activity. The average Mayo Wrist Score was 66.8 preoperatively and 70.9 postoperatively (p = 0.158). The average postoperative PRWE was 20.5, and average postoperative DASH was 15.1. At final follow-up, four patients had no radiographic evidence of arthritis. Two patients had evidence of early-stage radiocarpal arthritis, four had evidence of midcarpal arthritis, and two had radiographic evidence of mild scaphotrapeziotrapezoid arthritis. One patient required a salvage procedure with four-corner fusion.Discussion BLB reconstruction can be used to treat SL instability. At final follow-up, the majority of patients did not worsen clinically or functionally or require secondary salvage procedures; however, radiologic progression of arthritis was not prevented. These outcomes are comparable to midterm results of other SL reconstructive options; thus, we have abandoned this technique for other less technically demanding procedures.Level of Evidence IV
Keywords: bone-ligament-bone reconstruction; scapholunate instability; scapholunate injury; wrist pain